2020
DOI: 10.1104/pp.20.01054
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of a Cytochrome P450 Gene CYP94B1 by WRKY33 Transcription Factor Controls Apoplastic Barrier Formation in Roots to Confer Salt Tolerance

Abstract: Salinity is an environmental stress that causes decline in crop yield. Avicennia officinalis and other mangroves have adaptations such as ultrafiltration at the roots aided by apoplastic cell-wall barriers to thrive in saline conditions. We studied a Cytochrome P450 gene from A. officinalis, AoCYP94B1, and its putative ortholog in Arabidopsis (Arabidopsis thaliana), AtCYP94B1, which are involved in apoplastic barrier formation. Both genes were induced by 30 minutes of salt treatment in the roots. Heterologous … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
64
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 71 publications
(73 citation statements)
references
References 75 publications
2
64
0
Order By: Relevance
“…Among the transcription factors with the spatio-temporal expression patterns, about 32 and 49% were only differentially expressed at 3 h and 12 h after salt stress, respectively (Additional file 1: Figure S7a and b). Some of the transcription factors that were revealed to be responsive to salt stress previous studies were also detected in this study (Gao et al 2020;Krishnamurthy et al 2020;Xie et al 2010;Zhao et al 2019) (Additional file 1: Figure S7c).…”
Section: Transcription Factorsupporting
confidence: 76%
“…Among the transcription factors with the spatio-temporal expression patterns, about 32 and 49% were only differentially expressed at 3 h and 12 h after salt stress, respectively (Additional file 1: Figure S7a and b). Some of the transcription factors that were revealed to be responsive to salt stress previous studies were also detected in this study (Gao et al 2020;Krishnamurthy et al 2020;Xie et al 2010;Zhao et al 2019) (Additional file 1: Figure S7c).…”
Section: Transcription Factorsupporting
confidence: 76%
“…4D). Among these elements, sodium was previously proposed to be directly affected by suberin and salt treatments were previously shown to induce suberization (6, 22, 4345). This suggested that endodermal suberin induction in response to salt stress represents a protective mechanism against sodium entrance in plants.…”
Section: Resultsmentioning
confidence: 99%
“…So far, MYB39 and MYB41 are shown to regulate suberin formation (Cohen et al, 2020;Kosma et al, 2014). However, several CYP family genes are known to have the WRKY binding domains (W-box) in their promoter regions (Birkenbihl et al, 2017;Krishnamurthy et al, 2020;Xu et al, 2004). In a recent study, we showed that WRKY33 controls suberin formation by regulating CYP94B1 leading to enhanced salt tolerance of Arabidopsis and rice (Krishnamurthy et al, 2020).…”
Section: Introductionmentioning
confidence: 97%
“…Until recently, CYP94B family members were known to be involved in the initial ω-oxidation of jasmonic acid isoleucine (JA-Ile) to 12hydroxy jasmonic acid isoleucine (12OH-JA-Ile) affecting the JA signaling (Heitz et al, 2012;Kitaoka et al, 2011;Koo et al, 2011Koo et al, , 2014. However, in a recent study, we showed that CYP94B1 has a role in suberin biosynthesis (Krishnamurthy et al, 2020). Despite the increasing advances in understanding suberin biosynthesis and deposition, studies on the molecular mechanism regulating the genes involved in suberin formation are scarce.…”
Section: Introductionmentioning
confidence: 98%